Cytotoxicity and effect on wound re‐epithelialization after topical administration of tranexamic acid. Issue 6 (26th September 2019) - Eikebrokk, T. A.; Vassmyr, B. S.; Ausen, K.; Gravastrand, C.; Spigset, O.; Pukstad, B.
Abstract : Background: Topical administration of tranexamic acid (TXA) reduces bleeding from surgical wounds similarly to intravenous use, but with negligible risk of adverse systemic events. Topical use is expanding, but is off‐label. Surgeons lack guidelines regarding safe topical dosages and modes of administration. The effects of topical TXA on skin cells and wound healing are unknown. This study investigated whether topical TXA might be cytotoxic or affect wound re‐epithelialization. Methods: Human keratinocytes and fibroblast cell cultures and an ex vivo human skin wound model were subjected to both short (limited) and long (chronic) exposure to various clinically relevant concentrations of TXA to mimic different modalities of topical administration. Cytotoxicity and effects on wound re‐epithelialization were evaluated. Results: In cell culture, toxicity from chronic exposure was associated with increasing concentration and exposure time. Limited exposure to TXA did not cause significant cytotoxicity even at high concentrations. Re‐epithelialization was completely absent in wounds chronically exposed to TXA concentrations of 25 mg/ml or above, and 50–100 mg/ml induced epidermolysis of normal epithelium, possibly by a non‐toxic mechanism. Wound re‐epithelialization was slightly delayed, but not impaired, by limited exposure to 100 mg/ml or chronic exposure to 6·25 mg/ml. Conclusion: Although short exposure to even high concentrations of topical TXA seems well tolerated in vitro, prolonged exposure can be cytotoxic and may affect wound re‐epithelialization. Surgeons should adjust the TXA concentration to the planned mode of topical administration in clinical practice. Surgical relevance Topical tranexamic acid (TXA) may reduce bleeding from surgical wounds similarly to intravenous administration without the risk of systemic effects. Little is known, however, regarding the adverse effects of TXA on exposed tissues. We exposed in vitro human keratinocytes and fibroblasts and an ex vivo human skin wound model to TXA at various concentrations and time intervals and found that short exposure to even high concentrations or prolonged exposure to low concentrations of TXA was well tolerated. Prolonged exposure to increasing concentrations increased keratinocyte and fibroblast toxicity, and TXA concentrations of 25 mg/ml or above completely prevented wound‐re‐epithelialization. Prolonged exposure to high concentrations of topical TXA may exert unwanted local tissue effects. This study suggests that surgeons should adjust TXA concentration to the planned mode of topical administration in clinical practice. Abstract : Topical tranexamic acid reduces bleeding from surgical wounds, but little is known about possible adverse effects on the exposed tissue. In this experimental study, prolonged in vitro exposure was cytotoxic to keratinocytes and fibroblasts, and prevented wound re‐epithelialization in a dose‐dependent manner, whereas short exposure was well tolerated even at high concentrations. Correct concentration of topical tranexamic acid is the key Abstract : Antecedentes: La administración tópica de ácido tranexámico ( tranexamic acid, TXA) reduce la hemorragia de las heridas quirúrgicas de forma equivalente a su uso endovenoso, pero con un riesgo insignificante de eventos adversos sistémicos. El uso tópico se está expandiendo, pero se realiza fuera de indicación. Los cirujanos no disponen de directrices sobre las dosis para uso tópico seguras y las formas de administración. Se desconocen los efectos del TXA tópico sobre las células de la piel y sobre la curación de las heridas. Nos propusimos investigar si el TXA tópico puede ser citotóxico o afectar la reepitelización de la herida. Métodos: Los cultivos de queratinocitos humanos y fibroblastos y un modelo ex vivo humano de herida en la piel se sometieron a una exposición corta (limitada) y larga (crónica) de varias concentraciones clínicamente relevantes de TXA para simular diferentes modalidades de administración tópica. Se evaluaron la citotoxicidad y los efectos sobre la reepitelización de la herida. Resultados: En los cultivos celulares, la toxicidad de la exposición crónica se correlacionó con el incremento de la concentración y el tiempo de exposición. La exposición limitada al TXA no causó toxicidad significativa incluso a elevadas concentraciones. No se observó reepitelización en heridas expuestas de forma crónica a concentraciones de TXA de 25 mg/ml o superiores, y 50‐100 mg/ml provocó epidermólisis del epitelio normal, posiblemente por un mecanismo no tóxico. La reepitelización de la herida se retrasó ligeramente, pero no se deterioró por una exposición limitada de 100 mg/ml o exposición crónica de 6, 25 mg/ml. Conclusión: Mientras que la exposición corta, incluso hasta concentraciones elevadas, de TXA tópico parecen ser bien toleradas in vitro, la exposición prolongada al TXA tópico puede ser citotóxica y afectar la reepitelización de la herida. Los cirujanos deben ajustar la concentración de TXA al modo previsto de administración tópica en la práctica clínica.